Electronic Properties of Antiperovskite Materials from State-of-the-Art Density Functional Theory - M. Bilal; S. Jalali-Asadabadi; Rashid Ahmad; Iftikhar Ahmad (Journal of Chemistry)
We present a review on the research developments on the theoretical electronic properties of the antiperovskite materials. The antiperovskite materials have perovskite type structure with the positions of cations and anions interchanged. The electronic structures are used to explain different physical properties of materials; therefore it is crucial to understand band structures and densities of states of materials for their effective use in technology. The theoretical results of the electronic structure of antiperovskites were discussed and compared with the available experimental results to measure the accuracy of the research done so far on these materials. The important physical properties of these compounds like magnetic properties and superconductivity are also highlighted. Nevertheless the thermoelectric properties of these materials are still unexplored except for a few reports which suggest that antiperovskite materials may be potential candidates for thermoelectric generators.